Nursing care in promoting self-care of patients with leg ulcers: an integrative review - Ana Paula Cardoso Tavares; Selma Petra Chaves Sá (Universidad de Alicante, 2017)
Objective: To identify the evidence on nursing care in promoting self-care of patients with leg ulcers. Method: This is an integrative literature review whose search was conducted in databases: LILACS, MEDLINE, IBECS, CENTRAL, SCIELO and BDENF. Inclusion criteria were: articles in Portuguese, English and Spanish in its entirety and online, published between 2010 to 2015. Exclusion criteria were: articles repeated in different databases and systematic reviews. After reviewing the publications in full as the established criteria, only four studies met the requirements. Results: In general, studies have shown that stimulus to self-care brought improved performance in physical activities, feelings of hope, security and independence, knowledge about the problem, change in lifestyle, improvement in quality of life and evolution in the healing process. Conclusion: It was possible to identify results conducive to the realization of nursing care in promoting self-care of patients with leg ulcers.